The Charter School Law in Massachusetts: Analysis, Commentary, Wish - Rubin, David I. (Radical Teacher, 2014)
Nowhere is the link between the right’s national political agenda and the privatization of public education clearer than in Massachusetts. In November 1995, just weeks before announcing that he would run for the U.S. Senate against the liberal Democratic incumbent John Kerry, Governor William Weld unveiled a truly radical plan for reshaping K-12 education that could make Massachusetts the testing ground for every weapon in the privatization arsenal.